6-(-4+9i)-(-1-i)=

Simple and best practice solution for 6-(-4+9i)-(-1-i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(-4+9i)-(-1-i)= equation:


Simplifying
6 + -1(-4 + 9i) + -1(-1 + -1i) = 0
6 + (-4 * -1 + 9i * -1) + -1(-1 + -1i) = 0
6 + (4 + -9i) + -1(-1 + -1i) = 0
6 + 4 + -9i + (-1 * -1 + -1i * -1) = 0
6 + 4 + -9i + (1 + 1i) = 0

Reorder the terms:
6 + 4 + 1 + -9i + 1i = 0

Combine like terms: 6 + 4 = 10
10 + 1 + -9i + 1i = 0

Combine like terms: 10 + 1 = 11
11 + -9i + 1i = 0

Combine like terms: -9i + 1i = -8i
11 + -8i = 0

Solving
11 + -8i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -8i = 0 + -11

Combine like terms: 11 + -11 = 0
0 + -8i = 0 + -11
-8i = 0 + -11

Combine like terms: 0 + -11 = -11
-8i = -11

Divide each side by '-8'.
i = 1.375

Simplifying
i = 1.375

See similar equations:

| x^2+2y-16=0 | | 2(x-3)+4(2x-2)=4(3-7x) | | 11.65/x=2.33 | | 5/9*99 | | -5x^4+5=0 | | 68x=180 | | 8x-4x=3(5-x) | | 5(h+3)=25 | | ?/4=12.4 | | 4x+48=3x+8 | | 3x^4+4x^2-15=0 | | 2x-11+3x-47=180 | | 2x+11+3x-47=180 | | 27+7x-2=11x+1 | | 6x-5=2+13 | | 2(x+3)=5+3y | | 9y+y=9y-5 | | 8x-40+2x+20=180 | | 5(h-2)=48 | | log(4x+124)=3 | | 0.09xX=145.62 | | 4.5d-3.2=-18.5 | | 7x-40+9y=180 | | 1/4x-2=-6x5/12 | | (12x+2)=(18x-2) | | 4x+2=2x+14whatisx | | (12x+2)+(18x-2)=360 | | 7z+1-z=1+5z+7 | | y+2=-75(x+1) | | 2x/45 | | x(t)=x+120(t-6) | | 2x=90-3x |

Equations solver categories